Insulating material for high-thermal-conductivity transformer and preparation method of insulating material

A composite insulating material with ultra-high molecular weight polyethylene and hexagonal boron nitride, enhanced by in-situ modified silica particles, addresses the challenge of maintaining thermal conductivity and mechanical strength in transformers, offering improved insulation and mechanical performance.

CN119161691AInactive Publication Date: 2024-12-20TIANJIN DAGANG INSULATION MATERIAL FACTORY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411413469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing insulating materials for transformers face challenges in achieving high thermal conductivity while maintaining mechanical strength and insulation performance, as adding thermally conductive fillers often compromises these properties.

Method used

A composite insulating material composed of ultra-high molecular weight polyethylene, bisphenol A epoxy resin, hexagonal boron nitride, carboxylated multi-walled carbon nanotubes, and thermoplastic polycarbonate, with in-situ modification of silica particles to enhance compatibility and reduce filler gaps, is prepared through a specific process involving ultrasonic treatment, gel spinning, and curing.

Benefits of technology

The material achieves high thermal conductivity, improved mechanical properties, and enhanced insulation performance, suitable for large-scale applications in transformers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161691A_ABST
    Figure CN119161691A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulating materials for transformers, and particularly discloses a high-thermal-conductivity insulating material for a transformer and a preparation method of the insulating material. The insulating material for the high-thermal-conductivity transformer is prepared from the following raw materials in parts by mass: 30 to 60 parts of epoxy chloropropane, 40 to 50 parts of bisphenol A, 1 to 5 parts of bisphenol A epoxy resin E41, 10 to 15 parts of ultrahigh molecular weight polyethylene, 1 to 5 parts of tetraethoxysilane, 1 to 5 parts of carboxylated multi-walled carbon nanotubes, 3 to 5.5 parts of hexagonal boron nitride, 5 to 20 parts of thermoplastic polycarbonate and 1.01 to 3.1 parts of curing agent. The obtained insulating material is high in heat conductivity coefficient, the heat transfer capacity is greatly enhanced, the insulating performance can be greatly improved, meanwhile, the insulating material is excellent in mechanical performance and high in impact strength, and the preparation method is simple and suitable for large-scale application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating materials for transformers, and in particular to an insulating material for high thermal conductivity transformers and a preparation method thereof. Background Art

[0002] A transformer is a device that uses the principle of electromagnetic induction to change AC voltage. In recent years, with the rapid development of my country's economy, people have higher and higher requirements for transformers, among which the quality of insulation materials directly determines the service life of the transformer.

[0003] Insulating materials, also known as dielectrics, are materials with high resistivity and low conductivity. Insulating materials can be used to isolate charged or different potential conductors so that current flows in a certain direction. In transformer products, insulating materials also play the role of heat dissipation, cooling, support, fixation, arc extinguishing, improving potential gradient, moisture and mildew resistance, and protecting conductors.

[0004] Epoxy resin is widely used in transformer insulation materials due to its good processing properties, high adhesion, low shrinkage, and good stability. However, the thermal conductivity (also known as thermal conductivity coefficient) of epoxy resin is low, making it difficult to remove the heat generated by the components of the transformer during operation, and making it difficult to reduce the temperature of the epoxy resin itself. Its application is limited in fields with high requirements for thermal conductivity and insulation, which has become a major problem restricting the service life and reliability of transformer components.

[0005] Improving the heat dissipation performance of thermally conductive insulating materials has become the focus of research. At present, thermally conductive fillers are generally added to epoxy resin to improve its thermal conductivity. Metal powders and carbon materials are often used to try to improve the thermal conductivity of epoxy resin, but they will have a significant negative impact on the insulation performance. For example, when only 1% carbon nanotubes are added, the resistivity of epoxy resin materials will drop by at least four orders of magnitude. High thermal conductivity inorganic fillers such as alumina, boron nitride, and silicon carbide have good thermal conductivity and can be used in transformers to facilitate heat dissipation, but if they are directly added to epoxy resin, the mechanical strength of the insulating material will be significantly reduced.

[0006] CN110016205A discloses an epoxy resin thermally conductive insulating material and a preparation method thereof, which enables the epoxy resin thermally conductive insulating material to have excellent thermal conductivity and insulating properties by adjusting the ratio between the particle sizes of three inorganic fillers with different particle size gradations, the dosage ratio of fillers with different particle sizes, and the selection of particle sizes.

[0007] CN113549301A discloses an epoxy resin ultra-high thermal conductive insulating material and a preparation method thereof. A filler with a smaller particle size is compounded with a filler with a larger particle size so that the small particles fill the gaps between the large particles and the total space filling rate of the filler is increased. The thermal expansion rate of the material is reduced by modifying the inorganic fillers with different particle sizes after mixing.

[0008] At present, how to improve the insulation performance of thermally conductive insulating materials, increase the thermal conductivity of the materials, reduce the mechanical defects of the materials, and increase their impact strength has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an insulating material for a high thermal conductivity transformer and a preparation method thereof.

[0010] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include, by mass, 30-60 parts of epichlorohydrin, 40-50 parts of bisphenol A, 1-5 parts of bisphenol A epoxy resin E44, 10-15 parts of ultra-high molecular weight polyethylene, 1-5 parts of tetraethyl orthosilicate, 1-5 parts of carboxylated multi-walled carbon nanotubes, 3-5.5 parts of hexagonal boron nitride, 5-20 parts of thermoplastic polycarbonate and 1.01-3.1 parts of a curing agent.

[0011] Preferably, its thermal conductivity is ≥1.5W / (m·K), and its volume resistivity is ≥1×10 16 Ω·cm.

[0012] Preferably, the molecular weight of the ultra-high molecular weight polyethylene is 1.5 million to 2.7 million.

[0013] Preferably, the epoxy equivalent of the bisphenol A epoxy resin E44 is 225-239 g / eq.

[0014] Preferably, the curing agent is at least one of phthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride and pyromellitic anhydride.

[0015] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0016] S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride and curing agent into paraffin oil, perform ultrasonic treatment at 60-70° C. for 1-2 hours, heat to 190-220° C. for 1-3 hours, perform gel spinning, extraction and hot drawing to obtain reinforced composite fibers;

[0017] S2, epichlorohydrin and ethyl orthosilicate are mixed evenly, bisphenol A is added thereto and stirred for 10-30 minutes, the system temperature is adjusted to 70-80°C, sodium hydroxide solution is added thereto dropwise under stirring, stirring is continued for 2-3 hours after the addition is completed, carboxylated multi-walled carbon nanotubes are added and stirred for 10-30 minutes, benzene is added and stirred for 10-20 minutes, the water layer is removed after standing, and the organic layer is subjected to reduced pressure distillation to remove benzene and volatiles to obtain a reinforced epoxy resin;

[0018] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and curing agent, stir at 100-150°C for 1-2h, with a stirring pressure of 10-20kPa, cast into a mold and cure.

[0019] Preferably, in S2, the concentration of the sodium hydroxide solution is 1-2 mol / L, and the mass ratio of the sodium hydroxide solution to bisphenol A is 40-60:40-50.

[0020] Preferably, the mass ratio of the curing agent used in S1 to the curing agent used in S3 is 0.01-0.1:1-3.

[0021] Preferably, in S1, the ultrasonic frequency is 10-20 kHz and the spinning temperature is 170-180°C.

[0022] Preferably, in S3, the specific operation of curing is as follows: after casting, the temperature is raised to 90-95° C. for curing for 1-2 hours, and then the temperature is raised to 150-170° C. for curing for 10-20 hours.

[0023] Beneficial effects:

[0024] In the spinning process of ultra-high molecular weight polyethylene, the hexagonal boron nitride is oriented in the fiber stretching process, and the bisphenol A epoxy resin E4 is used to effectively promote fiber stability and reorganization, which can effectively enhance creep resistance and reduce fiber strength damage. In the obtained reinforced composite fiber, the hexagonal boron nitride is distributed in a sheet-like orientation along the stretching direction, which can effectively hinder the conduction of current and present excellent electrical insulation. In combination with the reinforcing epoxy resin, the thermal conductivity of the insulating material can be significantly enhanced.

[0025] Since inorganic silica particles have poor compatibility with epoxy resin, agglomeration phenomenon is very likely to occur. The present invention disperses tetraethyl orthosilicate in epichlorohydrin, and in-situ modification is performed during the synthesis of epoxy resin, so that not only the generated silica particles have excellent compatibility with epoxy resin, and effectively enhance the toughness of epoxy resin, but also can be combined with carboxylated multi-walled carbon nanotubes, so that the multi-walled carbon nanotubes have extremely high bonding strength in epoxy resin, and further compounded with reinforced composite fibers, which can effectively solve the problem of inorganic particles generating a large number of gaps when dispersed, and compound the multi-walled carbon nanotubes in a hollow tube structure with hexagonal boron nitride in a lamellar structure, so that the overall thermal conductivity of the obtained insulating material is excellent, and at the same time, the limitation on the amount of inorganic filler used in the prior art is overcome, and the amount of inorganic filler added is greatly reduced, avoiding the problem of large viscosity of the system and inconvenience of casting due to large addition.

[0026] The insulating material obtained by the present invention has high thermal conductivity, greatly enhanced heat transfer capability, and can greatly improve insulation performance. At the same time, the insulating material has excellent mechanical properties, high impact strength, and a simple preparation method, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a comparison chart of the viscosity of the mixed material before molding in the preparation method of Example 5 and Comparative Examples 1-2 and the potting glue used in Comparative Example 3, and a comparison chart of the tensile strength of the insulating material obtained in Example 5 and Comparative Examples 1-2 and the product after curing of the potting glue used in Comparative Example 3.

[0028] Figure 2 This is a comparison chart of the bending strength and impact strength of the insulating materials obtained in Example 5, Comparative Examples 1-2, and the cured product of the potting glue used in Comparative Example 3.

[0029] Figure 3 This is a comparison chart of the volume resistivity and thermal conductivity of the insulating materials obtained in Example 5, Comparative Examples 1-2, and the product of the potting glue used in Comparative Example 3 after curing. DETAILED DESCRIPTION

[0030] The present invention will be further explained below in conjunction with specific embodiments.

[0031] The bisphenol A epoxy resin E44 used below was purchased from Jinan Haomou Chemical Co., Ltd., and its epoxy equivalent was 234 g / eq after inspection. The ultra-high molecular weight polyethylene used below was purchased from Zhejiang Mouding Chemical Materials Co., Ltd., and its average molecular weight was 2 million after inspection, and its melt flow rate (230°C, 5kg) was 2.0 g / 10 min.

[0032] Example 1

[0033] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials of the insulating material include: 30 kg of epichlorohydrin, 40 kg of bisphenol A, 1 kg of bisphenol A epoxy resin E44, 10 kg of ultra-high molecular weight polyethylene, 1 kg of tetraethyl orthosilicate, 1 kg of carboxylated multi-walled carbon nanotubes, 3 kg of hexagonal boron nitride, 5 kg of thermoplastic polycarbonate and 1.01 kg of phthalic anhydride.

[0034] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0035] S1. Ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.01 kg of phthalic anhydride were added to 50 kg of paraffin oil, and ultrasonically treated at 60 ° C for 1 h, with an ultrasonic frequency of 10 kHz, and heated to 190 ° C for 1 h, and gel-spun at a spinning temperature of 170 ° C, extracted, and hot-drawn to obtain a reinforced composite fiber with a diameter of 50 μm;

[0036] S2, epichlorohydrin and ethyl orthosilicate were mixed evenly, bisphenol A was added thereto, stirred at a speed of 100 r / min for 10 min, the system temperature was adjusted to 70°C, 40 kg of 1 mol / L sodium hydroxide solution was added thereto under stirring, stirring was continued for 2 h after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 10 min, 60 kg of benzene was added and stirred for 10 min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0037] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and 1 kg of phthalic anhydride, stir at 100°C for 1 hour, with a stirring pressure of 10 kPa, cast into a mold, cure at 90°C for 1 hour, and then heat to 150°C and cure for 10 hours.

[0038] Example 2

[0039] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 60 kg of epichlorohydrin, 50 kg of bisphenol A, 45 kg of bisphenol A epoxy resin E4, 15 kg of ultra-high molecular weight polyethylene, 5 kg of tetraethyl orthosilicate, 5 kg of carboxylated multi-walled carbon nanotubes, 5.5 kg of hexagonal boron nitride, 20 kg of thermoplastic polycarbonate, and 3.1 kg of pyromellitic anhydride.

[0040] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0041] S1. Ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.1 kg of pyromellitic anhydride were added to 80 kg of paraffin oil, and ultrasonically treated at 70 ° C for 2 h, with an ultrasonic frequency of 20 kHz, and heated to 220 ° C for 3 h, and gel-spun at a spinning temperature of 180 ° C, extracted, and hot-drawn to obtain a reinforced composite fiber with a diameter of 200 μm;

[0042] S2, epichlorohydrin and ethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 500r / min for 30min, the system temperature was adjusted to 80°C, 60kg of 2mol / L sodium hydroxide solution was added thereto under stirring, stirring was continued for 3h after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 30min, 100kg of benzene was added and stirred for 20min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0043] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and 3 kg of isophthalic anhydride, stir at 150°C for 2 h, stirring pressure of 20 kPa, pour into a mold, cure at 95°C for 2 h, then heat to 170°C for 20 h.

[0044] Example 3

[0045] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 40 kg of epichlorohydrin, 48 kg of bisphenol A, 442 kg of bisphenol A epoxy resin E, 13 kg of ultra-high molecular weight polyethylene, 2 kg of tetraethyl orthosilicate, 4 kg of carboxylated multi-walled carbon nanotubes, 3.5 kg of hexagonal boron nitride, 16 kg of thermoplastic polycarbonate, 0.07 kg of hexahydrophthalic anhydride, and 2.5 kg of methyltetrahydrophthalic anhydride.

[0046] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0047] S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.07 kg of hexahydrophthalic anhydride to 55 kg of paraffin oil, perform ultrasonic treatment at 68 ° C for 80 min, the ultrasonic frequency is 18 kHz, the temperature is raised to 200 ° C and kept for 2.5 h, gel spinning, the spinning temperature is 173 ° C, extraction, and hot drawing to obtain a reinforced composite fiber with a diameter of 100 μm;

[0048] S2, epichlorohydrin and ethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 200 r / min for 25 min, the system temperature was adjusted to 73 ° C, 55 kg of 1.2 mol / L sodium hydroxide solution was added thereto under stirring, and stirring was continued for 160 min after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 15 min, 90 kg of benzene was added and stirred for 12 min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0049] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and 2.5 kg of methyltetrahydrophthalic anhydride, stir at 120°C for 100 min, with a stirring pressure of 13 kPa, pour into a mold, cure at 93°C for 80 min, and then heat to 165°C for 13 h.

[0050] Example 4

[0051] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 50 kg of epichlorohydrin, 42 kg of bisphenol A, 44 kg of bisphenol A epoxy resin E, 11 kg of ultra-high molecular weight polyethylene, 4 kg of tetraethyl orthosilicate, 2 kg of carboxylated multi-walled carbon nanotubes, 5 kg of hexagonal boron nitride, 8 kg of thermoplastic polycarbonate, 0.03 kg of methyltetrahydrophthalic anhydride, and 1.5 kg of phthalic anhydride.

[0052] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0053] S1. Ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.03 kg of methyltetrahydrophthalic anhydride were added to 75 kg of paraffin oil, and ultrasonically treated at 62 ° C for 100 min with an ultrasonic frequency of 12 kHz. The temperature was raised to 210 ° C and kept for 1.5 h. Gel spinning was performed at a spinning temperature of 177 ° C, and extraction and hot drawing were performed to obtain a reinforced composite fiber with a diameter of 100 μm.

[0054] S2, epichlorohydrin and ethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 400r / min for 15min, the system temperature was adjusted to 77°C, 45kg of 1.8mol / L sodium hydroxide solution was added thereto under stirring, stirring was continued for 140min after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 25min, 70kg of benzene was added and stirred for 18min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0055] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and 1.5 kg of phthalic anhydride, stir at 140°C for 80 min, with a stirring pressure of 17 kPa, cast into a mold, cure at 91°C for 100 min, and then heat to 155°C for 17 h.

[0056] Example 5

[0057] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 45 kg of epichlorohydrin, 45 kg of bisphenol A, 3 kg of bisphenol A epoxy resin E44, 12 kg of ultra-high molecular weight polyethylene, 3 kg of tetraethyl orthosilicate, 3 kg of carboxylated multi-walled carbon nanotubes, 4 kg of hexagonal boron nitride, 12 kg of thermoplastic polycarbonate, 0.05 kg of phthalic anhydride and 2 kg of pyromellitic anhydride.

[0058] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0059] S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.05 kg of phthalic anhydride to 65 kg of paraffin oil, perform ultrasonic treatment at 65 ° C for 90 min, the ultrasonic frequency is 15 kHz, the temperature is raised to 205 ° C and kept for 2 h, gel spinning, the spinning temperature is 175 ° C, extraction, and hot drawing to obtain a reinforced composite fiber with a diameter of 100 μm;

[0060] S2, epichlorohydrin and ethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 300r / min for 20min, the system temperature was adjusted to 75°C, 50kg of 1.5mol / L sodium hydroxide solution was added thereto under stirring, stirring was continued for 150min after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 20min, 80kg of benzene was added and stirred for 15min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0061] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and 2 kg of pyromellitic anhydride, stir at 130°C for 90 min and 15 kPa, pour into a mold, cure at 92°C for 90 min, and then heat to 160°C for 15 h.

[0062] Comparative Example 1

[0063] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 45 kg of epichlorohydrin, 45 kg of bisphenol A, 3 kg of bisphenol A epoxy resin E44, 12 kg of ultra-high molecular weight polyethylene, 3 kg of tetraethyl orthosilicate, 3 kg of carboxylated multi-walled carbon nanotubes, 4 kg of hexagonal boron nitride, 12 kg of thermoplastic polycarbonate, 0.05 kg of phthalic anhydride and 2 kg of pyromellitic anhydride.

[0064] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0065] S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride, and 0.05 kg of phthalic anhydride to 65 kg of paraffin oil, perform ultrasonic treatment at 65 ° C for 90 min, the ultrasonic frequency is 15 kHz, the temperature is raised to 205 ° C and kept for 2 h, gel spinning, the spinning temperature is 175 ° C, extraction, and hot drawing to obtain a reinforced composite fiber with a diameter of 100 μm;

[0066] S2, epichlorohydrin and tetraethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 300r / min for 20min, the system temperature was adjusted to 75°C, 50kg of 1.5mol / L sodium hydroxide solution was added thereto under stirring, and stirring was continued for 150min after the addition was completed, 80kg of benzene was added and stirred for 15min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0067] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate, carboxylated multi-walled carbon nanotubes and 2 kg of pyromellitic anhydride, stir at 130°C for 90 min, with a stirring pressure of 15 kPa, cast into a mold, and cure at 92°C for 90 min, then heat to 160°C and cure for 15 h.

[0068] Comparative Example 2

[0069] The invention discloses an insulating material for a high thermal conductivity transformer. The raw materials thereof include: 45 kg of epichlorohydrin, 45 kg of bisphenol A, 3 kg of bisphenol A epoxy resin E44, 12 kg of ultra-high molecular weight polyethylene, 3 kg of tetraethyl orthosilicate, 3 kg of carboxylated multi-walled carbon nanotubes, 4 kg of hexagonal boron nitride, 12 kg of thermoplastic polycarbonate, 0.05 kg of phthalic anhydride and 2 kg of pyromellitic anhydride.

[0070] The method for preparing the insulating material for the high thermal conductivity transformer comprises the following steps:

[0071] S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, and 0.05 kg of phthalic anhydride to 65 kg of paraffin oil, perform ultrasonic treatment at 65 ° C for 90 min, the ultrasonic frequency is 15 kHz, the temperature is raised to 205 ° C and kept for 2 h, gel spinning is performed at a spinning temperature of 175 ° C, extraction is performed, and hot drawing is performed to obtain a reinforced composite fiber with a diameter of 100 μm;

[0072] S2, epichlorohydrin and ethyl orthosilicate were mixed uniformly, bisphenol A was added thereto, stirred at a speed of 300r / min for 20min, the system temperature was adjusted to 75°C, 50kg of 1.5mol / L sodium hydroxide solution was added thereto under stirring, stirring was continued for 150min after the addition was completed, carboxylated multi-walled carbon nanotubes were added and stirred for 20min, 80kg of benzene was added and stirred for 15min, the water layer was removed by standing, the organic layer was separated, and benzene and volatiles were removed by reduced pressure distillation to obtain a reinforced epoxy resin;

[0073] S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate, hexagonal boron nitride and 2 kg of pyromellitic anhydride, stir at 130°C for 90 min and a stirring pressure of 15 kPa, pour into a mold, cure at 92°C for 90 min, and then heat to 160°C for curing for 15 h.

[0074] Comparative Example 3

[0075] Use JT8968 potting glue from Jiangte Insulation Materials Company.

[0076] The viscosity of the mixed materials before molding in the preparation methods of Example 5 and Comparative Examples 1-2 and the potting glue used in Comparative Example 3 were tested using a rotational rheometer. The viscosity of each sample was tested at 70° C. using a parallel plate rotor and DMA shear mode at a frequency of 1 Hz.

[0077] With reference to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", the tensile strength of the insulating materials obtained in Example 5, Comparative Examples 1-2, and the product after curing of the potting glue used in Comparative Example 3 were measured.

[0078] With reference to GB / T 9341-2008 “Determination of flexural properties of plastics”, the flexural strength of the insulating materials obtained in Example 5 and Comparative Examples 1-2 and the cured product of the potting glue used in Comparative Example 3 were measured.

[0079] With reference to GB / T 1843-2008 “Determination of Izod Impact Strength of Plastics”, the impact strengths of the insulating materials obtained in Example 5 and Comparative Examples 1-2 and the cured product of the potting glue used in Comparative Example 3 were measured.

[0080] like Figure 1 and Figure 2 As shown, the viscosity of the mixed material before molding in the preparation methods of Example 5 and Comparative Examples 1-2 and the potting glue used in Comparative Example 3 are both less than 1 Pa·s, and can be used for casting applications of electrical equipment such as transformers; while the viscosity of the mixed material before molding in the preparation methods of Example 5 and Comparative Examples 1-2 is significantly lower than that of the potting glue used in Comparative Example 3, and can better meet the casting requirements.

[0081] The mechanical properties of the insulating material obtained in Example 5 are the highest, which are better than those of the insulating materials obtained in Comparative Examples 1-2 and the product after curing of the potting glue used in Comparative Example 3 (P<0.05).

[0082] Keithley 8009 resistance test box was used to test the DC volume resistivity of the insulating materials obtained in Example 5, Comparative Examples 1-2, and the product after curing of the potting glue used in Comparative Example 3. The samples were all 1 mm thick discs, and the test voltage was 1000V.

[0083] A thermal conductivity analyzer was used to test the thermal conductivity of the insulating materials obtained in Example 5, Comparative Examples 1-2, and the cured product of the potting glue used in Comparative Example 3. The test method was the transient plane heat source (MTPS) method, and the samples were all discs with a thickness of 3 mm.

[0084] like Figure 3 As shown, the volume resistivity and thermal conductivity of the insulating material obtained in Example 5 are both the highest, which are better than the insulating materials obtained in Comparative Examples 1-2 and the product after curing of the potting glue used in Comparative Example 3 (P<0.05).

[0085] The applicant believes that the reason for the above results is that, in the spinning process of ultra-high molecular weight polyethylene, the hexagonal boron nitride is oriented in the fiber stretching process, and the bisphenol A epoxy resin E4 is used to effectively promote fiber stability and reorganization, which can effectively enhance creep resistance and reduce fiber strength damage. In the obtained reinforced composite fiber, the hexagonal boron nitride is distributed in a sheet-like orientation along the stretching direction, which can effectively hinder the conduction of current and present excellent electrical insulation. In combination with the reinforcing epoxy resin, the thermal conductivity of the insulating material can be significantly enhanced. At the same time, the present invention disperses tetraethyl orthosilicate in epichlorohydrin and performs in-situ modification during the synthesis of epoxy resin. Not only are the generated silicon dioxide particles extremely compatible with the epoxy resin and effectively enhance the toughness of the epoxy resin, but they can also be combined with carboxylated multi-walled carbon nanotubes, so that the multi-walled carbon nanotubes have extremely high bonding strength in the epoxy resin. Further compounding with reinforced composite fibers can effectively solve the problem of a large number of gaps generated when inorganic particles are dispersed, and the multi-walled carbon nanotubes with a hollow tube structure are compounded with hexagonal boron nitride with a lamellar structure, so that the overall thermal conductivity of the obtained insulating material is excellent. The limitation on the amount of inorganic filler used in the prior art is also overcome, the amount of inorganic filler added is greatly reduced, and the problem of high viscosity of the system and inconvenience in casting due to a large amount of added is avoided.

[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An insulating material for a high thermal conductivity transformer, characterized in that: The raw materials include, by mass, 30-60 parts of epichlorohydrin, 40-50 parts of bisphenol A, 1-5 parts of bisphenol A type epoxy resin E44, 10-15 parts of ultra-high molecular weight polyethylene, 1-5 parts of tetraethyl orthosilicate, 1-5 parts of carboxylated multi-walled carbon nanotubes, 3-5.5 parts of hexagonal boron nitride, 5-20 parts of thermoplastic polycarbonate and 1.01-3.1 parts of curing agent.

2. The insulating material for a high thermal conductivity transformer according to claim 1, characterized in that: Its thermal conductivity is ≥1.5W / (m·K), and its volume resistivity is ≥1×10 16 Ω·cm.

3. The insulating material for a high thermal conductivity transformer according to claim 1, characterized in that: The molecular weight of ultra-high molecular weight polyethylene is 1.5 million to 2.7 million.

4. The insulating material for a high thermal conductivity transformer according to claim 1, characterized in that: The epoxy equivalent of bisphenol A epoxy resin E44 is 225-239 g / eq.

5. The insulating material for a high thermal conductivity transformer according to claim 1, characterized in that: The curing agent is at least one of phthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride and pyromellitic anhydride.

6. A method for preparing the insulating material for a high thermal conductivity transformer according to any one of claims 1 to 5, characterized in that: The steps include: S1. Add ultra-high molecular weight polyethylene, bisphenol A epoxy resin E44, hexagonal boron nitride and curing agent into paraffin oil, perform ultrasonic treatment at 60-70° C. for 1-2 hours, heat to 190-220° C. for 1-3 hours, perform gel spinning, extraction and hot drawing to obtain reinforced composite fibers; S2, epichlorohydrin and ethyl orthosilicate are mixed evenly, bisphenol A is added thereto and stirred for 10-30 minutes, the system temperature is adjusted to 70-80°C, sodium hydroxide solution is added thereto dropwise under stirring, stirring is continued for 2-3 hours after the addition is completed, carboxylated multi-walled carbon nanotubes are added and stirred for 10-30 minutes, benzene is added and stirred for 10-20 minutes, the water layer is removed after standing, and the organic layer is subjected to reduced pressure distillation to remove benzene and volatiles to obtain a reinforced epoxy resin; S3. Evenly mix the reinforced epoxy resin, reinforced composite fiber, thermoplastic polycarbonate and curing agent, stir at 100-150°C for 1-2h, with a stirring pressure of 10-20kPa, cast into a mold and cure.

7. The method for preparing the insulating material for high thermal conductivity transformer according to claim 6, characterized in that: In S2, the concentration of the sodium hydroxide solution is 1-2 mol / L, and the mass ratio of the sodium hydroxide solution to bisphenol A is 40-60:40-50.

8. The method for preparing the insulating material for high thermal conductivity transformer according to claim 6, characterized in that: The mass ratio of the curing agent used in S1 to the curing agent used in S3 is 0.01-0.1:1-3.

9. The method for preparing the insulating material for high thermal conductivity transformer according to claim 6, characterized in that: In S1, the ultrasonic frequency is 10-20 kHz and the spinning temperature is 170-180°C.

10. The method for preparing the insulating material for high thermal conductivity transformer according to claim 6, characterized in that: In S3, the specific operation of curing is as follows: after casting, the temperature is raised to 90-95°C for curing for 1-2 hours, and then the temperature is raised to 150-170°C for curing for 10-20 hours.

Citation Information

Patent Citations

  • Graphene ultrahigh-molecular-weight polyethylene hybrid fiber

    CN105420833A

  • Antistatic epoxy resin-based heat dissipation powder coating and preparation method thereof

    CN105907258A

  • Epoxy-based insulating and heat-conducting composite material and preparation method thereof

    CN115558237A

  • High-temperature-resistant anti-aging electronic packaging resin and preparation method thereof

    CN117165234A

  • Preparation method and application of ultra-high molecular weight polyethylene and carbon nanotube composite fiber

    CN117626638A